Fonio millet genome unlocks African orphan crop diversity for agriculture in a changing climate - Michael Abrouk (Nature Communications, 2020)
Fonio millet is a fast growing orphan cereal crop with a great potential for dryland agriculture. Here, the authors report chromosome-scale reference genome assembly and population genomic resources to shed light on genetic diversity, population structure and domestication of fonio millet.